Russia's Economic Landscape: Navigating Recession, Inflation, and Sanctions - Gubad Ibadoghlu (ZBW - Leibniz Information Centre for Economics, 2024)
This article analyzes the current state of the Russian economy, which is characterized by a complex interplay of overheating, inflationary pressures, and the impact of international sanctions. Despite moderate GDP growth and low unemployment, the economy faces significant vulnerabilities, including rising inflation, declining investment activity, and a depreciating ruble. The Central Bank of Russia's policy of maintaining high interest rates, intended to stabilize the currency and control inflation, has inadvertently constrained economic growth and heightened uncertainty for businesses. These challenges are further exacerbated by shifts in foreign trade dynamics, with declining exports and imports reducing the balance of payments surplus. Western-imposed sanctions continue to target Russia's energy sector, implementing measures such as oil price caps and restrictions on Gazprombank. While these sanctions aim to undermine the Russian economy, previous efforts at localization have partially mitigated their impact, allowing the country to sustain energy revenue streams. Nevertheless, the prioritization of military expenditures, surpassing budgetary allocations for social policies, healthcare, and education, risks destabilizing public finances and undermining social commitments. The interaction of geopolitical tensions, energy revenues, and evolving sanctions will play a decisive role in shaping Russia's economic future. This study offers a comprehensive analysis of macroeconomic indicators, trade dynamics, and fiscal imbalances, providing valuable insights into the uncertainties facing the Russian economy.
Keywords: 330; Russian economy; Russian ruble; inflationary pressures; sanctions; Central Bank of Russia; energy sector; fiscal policy; trade dynamics; macroeconomic indicators; geopolitical tensions